Desempenho de escolares de ensino público com e sem dificuldade de aprendizagem em habilidadefonológica, nomeação rápida, leitura e escrita - Capellini, Simone Aparecida [UNESP] (2011)
Purpose: characterizing and comparing the performance of students with and without learning difficulties from the public education in phonological awareness, rapid naming, reading and writing. Methods: sixty private students from 2nd to 4th grades participated, distributed into six groups – each one was composed of 10 students being three groups of students without learning difficulties and three groups with such difficulties. As procedure phonological awareness, rapid naming and oral reading and writing under dictation were used. Results: the results highlighted a superior development of those without learning difficulties compared to the students with learning difficulties. Conclusion: the students with learning difficulties presented a higher score in the time/speed task of rapid naming and, consequently, lower production in activities of phonological awareness and reading and writing, when compared to students without difficulties. Thus, a relation between rapid naming and lexical access is revealed, as well as between visual discrimination, frequency of word occurrence and presentation of the code naming needed to do the phoneme-grapheme conversion process required in the reading and writing in an alphabetic writing system such as the Portuguese language.